1996
DOI: 10.1209/epl/i1996-00210-x
|View full text |Cite
|
Sign up to set email alerts
|

Shell structure and electron-electron interaction in self-assembled InAs quantum dots

Abstract: Using far-infrared spectroscopy, we investigate the excitations of selforganized InAs quantum dots as a function of the electron number per dot, 1 ≤ n e ≤ 6, which is monitored in situ by capacitance spectroscopy. Whereas the well-known two-mode spectrum is observed when the lowest (s-) states are filled, we find a rich excitation spectrum for n e ≥ 3, which reflects the importance of electron-electron interaction in the present, strongly non-parabolic confining potential. From capacitance spectroscopy we find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
150
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(168 citation statements)
references
References 27 publications
16
150
0
2
Order By: Relevance
“…These values are close to the ones used 21 to describe the rings studied by Lorke et al 3 The electron effective mass m*ϭ0.063 ͑we write m ϭm*m e with m e being the physical electron mass͒ and effective gyromagnetic factor g*ϭϪ0.43 have been taken from the experiments, [32][33][34] and the value of the dielectric constant has been taken to be ⑀ϭ12.4. The model is strictly two-dimensional, and as a consequence of circular symmetry, the single particle ͑s.p.͒ wave functions are eigenstates of the orbital angular momentum l z and can be written as u nl (r) Figure 1 shows the addition energies ⌬ 2 (N) at zero magnetic field.…”
Section: Ground State Resultssupporting
confidence: 69%
“…These values are close to the ones used 21 to describe the rings studied by Lorke et al 3 The electron effective mass m*ϭ0.063 ͑we write m ϭm*m e with m e being the physical electron mass͒ and effective gyromagnetic factor g*ϭϪ0.43 have been taken from the experiments, [32][33][34] and the value of the dielectric constant has been taken to be ⑀ϭ12.4. The model is strictly two-dimensional, and as a consequence of circular symmetry, the single particle ͑s.p.͒ wave functions are eigenstates of the orbital angular momentum l z and can be written as u nl (r) Figure 1 shows the addition energies ⌬ 2 (N) at zero magnetic field.…”
Section: Ground State Resultssupporting
confidence: 69%
“…As di scussed i n Ref. [16], the two -dim ensional mo del i s to o p oor fo r the self -assembl ed QD s; m oreo ver, the brea ki ng of the general i zed Ko hn theo rem [33,34], observed i n the self-assembl ed QD s [35], suggests tha t the conÙnem ent p otenti al signi Ùcantl y di˜ers fro m the pa ra b oli c p otenti al . For the self-assembl ed QD s, the m odel conÙning potenti al s i n the form of the Ùnite recta ng ul ar p otenti al well [15] and the G aussian p otenti al [25] m uch b etter account f or the conducti on-ba nd o˜set at the InAs/ G aAs i nterf ace and the varyi ng com p ositi on wi thi n the InG aAs do ts [36].…”
Section: Self-assembled Quant Um Dotsmentioning
confidence: 88%
“…In this particular case ͑i.e., Qϭ1), the heavy-holes ground state energies of the cubes are the same, to within 5%, as those of the pyramids, for 66 ÅϽV 1/3 Ͻ150 Å, which is the region of interest, in which the typical ͑uniformly sized and distributed͒ experimental selfassembled pyramidal dot dimensions range. [17][18][19][20][21] Nevertheless we have found that even for structures of a given shape and volume, E gs varies depending on the particular aspect ratio Q of the dot. This variation is volume dependent in the sense that the range of Q within which ⌬E gs ϭ͓E gs (Q) ϪE gs (Qϭ1)͔/E gs (Q) ͑i.e., the percentual variation of the ground state energy of a structure with a given Q, relative to that of a structure with Qϭ1) is, say, 3%, is smaller for small volumes than it is for large volumes.…”
Section: Resultsmentioning
confidence: 80%